PARASITIC HELMINTHIASIS: CLINICAL AND DIAGNOSTIC ASPECTS OF ECHINOCOCCOSIS AND TRICHOCEPHALOSIS (Journal of Universal Science Research, 2026)
This article discusses helminthiasis (worm diseases) in children, their etiology, transmission routes, clinical symptoms, and modern methods of diagnosis and prevention. The article provides information on the main symptoms of the disease, diagnostic methods, including laboratory tests and modern methods, for the example of such common helminthiasis as helminthiasis, echinococcosis, and trichocephalosis